CASH WAQF FOR MICROFINANCE: A BIBLIOMETRIC ANALYSIS - Aini, Zahriya Nurul (Jurnal Ekonomi dan Bisnis Airlangga, 2024)
Introduction: Waqf is one of the Islamic social financial instruments, having the distinctive characteristic that waqf assets are donated voluntarily by the wakif and are permanently designated for social benefits. Waqf can be used for productive or commercial activities to generate profits by Sharia law. Cash waqf can play a role in supporting the overall development process, both in human resource development, as well as in economic and social development. This study tries to explore the role of cash waqf for microfinance which can subsequently help the people's economy. Methods: The research method used in this research is quantitative research with bibliometric analysis. Data sources collected secondary data obtained from the Google Scholar database. Data were obtained using Publish or Perish (POP) software and analyzed using VOSviewer software. Results: The results of this research show that, from data searches using the keywords "cash waqf", "microfinance" and "sharia microfinance" by limiting 500 papers in the 2010-2024 time period, the words "microfinance institutions" are the most frequent keywords, indicated by a darker color than other keywords. Conclusion and suggestion: Based on the results and analysis, it can be concluded that, from year to year, research on the topic of cash waqf for microfinance is most often used. However, research on the topic of cash waqf for Sharia microfinance is still limited. Therefore, future research can be carried out regarding cash waqf for sharia microfinance. Cash waqf plays an important role in supporting the overall development process, both in human resource development, as well as in economic and social development. The potential of cash waqf can be used as a means of economic empowerment for lower-middle-class communities with the role played by microfinance institutions.